A Nash threat game of passing through Exchange Rate Mechanism II - Christian Fahrholz (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Following entrance into the European Union, Central Eastern European Countries (CEECs) are expected to join the European Monetary Union (EMU). These countries may incur considerable costs over the course of their passing through the required Exchange Rate Mechanism II (ERM-II). However, with enough bargaining leverage CEECs may be able to pass some of these costs on to current EMU-members. In turn, a CEECs leverage depends on their ability to wield successful brinkmanship via an exchange-rate policy characterized by a threaten-thy-neighbor strategy. A two-stage Nash-threat game captures the essentials of the CEECs phase of ERM-II pass through.
Keywords: C72; C78; F33; F51; 330; Threat game; Nash-bargaining solution; exchange-rate policy; EU-enlargement; EMU; Europäischer Währungsverbund; Konvergenzkriterien; Soziale Kosten; EU-Erweiterung; Europäische Wirtschafts- und Währungsunion; Verhandlungen; Nash-Gleichgewicht; EU-Staaten (Osteuropa); EU-Staaten